A city burdened with unplanned overpasses: a grounded theory approach to identify the root cause for its implementation - Mubassirah, Fabiha Atique (Kansas State University, 2019)
The most crucial urban problem in Dhaka, the capital of Bangladesh, is its traffic congestion. The absence of adequate transportation planning and lack of proper integration between infrastructure management bodies have resulted in motionless streets in Dhaka, where vehicles remain frozen on roads for hours. The government of Bangladesh is constructing flyovers or overpasses which are full-grade separations in major intersections of Dhaka. Eight flyovers have already been constructed so far to curb the congestion problem, and to eliminate conflicts between rail-road traffic and potential accidents. But, unfortunately, most of them resulted in poor performance and inefficiency in mitigating congestion. These transportation infrastructure projects have not only deteriorated the traffic condition of the city, but they impede the potential for other long-term sustainable options. Flyover construction is an expensive project for a developing country like Bangladesh, and there could have been several alternative reasonable solutions which were overlooked. This situation necessitates digging into the root causes for the selection and implementation of flyover projects in Dhaka. The study aims to identify the reasons why the government of Bangladesh is implementing flyover projects in Dhaka. A grounded theory approach has been followed to inductively derive a theory behind the reason of this flyover scenario. Content analysis and interviews of the stakeholders and policy makers have been done to collect the data. The theory derived in the research provides an explanation for the root cause of the present traffic disaster. The analysis reveals that weak governance of Bangladesh which includes political decision-making and ineffective institutional framework motivated this infrastructure failure in Dhaka.
Keywords: Flyover; Overpass; Dhaka; Grounded Theory; Infrastructure; Transportation Planning